URGENSITAS PENDIDIKAN BERBASIS TAUHID DI LEMBAGA PENDIDIKAN ISLAM - Muhammad Yusuf Pulungan (IAIN Padangsidimpuan, 2018)
Nowadays, science is expanding more advances. The expansion produces out a very rapid technology so that human being can get many easier and huge lifes. An advance science isn’t almost escorted by meaningful humanity awareness. Even in an advance country always spared from science and technology problems that appeared inside. The citizens tend to be materialist, individualist, and far lose in doing religious of moral values. It’s almost right that “Even science and technology may give a better quality of human life, however not source represent a skill-even less an absolute value of something behave. Why’s wrong? It can be because of tauhid basic or divinity of education systems now has been ignored or didn’t integrate in education process.”